Pengembangan sistem informasi presensi perangkat desa berbasis website - David, Erwin; Swalaganata, Galandaru (Universitas Merdeka Malang, 2023)
The development of information technology requires government agencies to participate and adapt. The village government is one of the agencies affected by implementing information technology. Tambang Bunut Village is experiencing problems in managing attendance data which is still manual. Manual attendance causes many data discrepancies, such as falsified data, missing data, and also data that is not recorded. In addition, the manual system causes attendance recap time to take longer and be inefficient. This study uses a prototype development model consisting of needs analysis, system feasibility analysis, and process design. The results of this study are a website-based village apparatus presence information system managed by one administrator. The testing results of system functionality indicate that the presence information system is feasible to use and can be well received by users. Apart from being assessed in terms of efficiency in displaying data and shortening the time for reporting employee attendance, this information system is also able to reduce village budget spending in presence system operations.